The mediating role of cardiac patients' perception of nursing care on the relationship between kinesiophobia, anxiety and depression in rural hospitals: a cross-sectional study - Mohamed Hussein Ramadan Atta; Shimmaa Mohamed Elsayed; Sharaf Omar Al Shurafi; Rasha Salah Eweida (BMC, 2024)
Abstract Background Kinesiophobia could act as a significant barrier against physical activity following cardiac procedures worsening cardiovascular health problems and potentially leading to conditions like hospital-acquired anxiety and depression among patients with cardiovascular disease (CVD). Nurses are the vanguard health care team who can aid patients in taking proactive steps to overcome fear of movement following cardiac procedures. Aim The overarching aim is to investigate the relationship between kinesiophobia, anxiety and depression, and patients' perception of nursing care. Method A descriptive correlational research design in two rural hospitals, conducted at cardiac intensive care units of Kafr Eldawar Hospital and Damanhur Medical National Institute. Data were collected from 265 nurses, using the following patient-reported outcome measures, the Tampa Scale for Kinesiophobia (TSK), the Hospital Anxiety and Depression Scale (HADS), the Person-Centered Critical Care Nursing Questionnaire (PCCNP) and the patients' demographic and clinical profile. Result A significant negative correlation was found between HADS and PCCNP (r: -0.510, p < 0.001) however, Kinesiophobia was significantly and positively correlated (r: 0.271, p < 0.001). A direct effect of PCCNP in the presence of the mediator was found to be not statistically significant (-0.015, CR = 0.302, p = 0.763). Nonetheless, PCCNP indirectly affects kinesiophobia through HADS (p=-0.099). Implication for nursing practice Customizing individualized cardiac rehabilitation (CR) programs based on the emotional experience of cardiac patients will be conducive to rehabilitation and prognosis for patients, thereby lessening the physical burden and improving their quality of life.